The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/gtc.12149
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of satellite I noncoding RNA in regulation of chromosome segregation

Abstract: Human centromeres consist of repetitive sequences from which satellite I noncoding RNAs are transcribed. We found that knockdown of satellite I RNA causes abnormal chromosome segregation and generation of nuclei with a grape-shape phenotype. Co-immunoprecipitation experiments showed that satellite I RNA associates with Aurora B, a component of the chromosome passenger complex (CPC) regulating proper attachment of microtubules to kinetochores, in mitotic HeLa cells. Satellite I RNA was also shown to associate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
103
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(114 citation statements)
references
References 31 publications
(62 reference statements)
11
103
0
Order By: Relevance
“…My results suggest that a high local concentration of centromeric lncRNAs on mitotic centromeres and chromosomes is an additional pathway for CPC localization and activation that acts in parallel to known pathways of CPC recruitment. Additionally, my results suggest that the CPC is one of the major mitotic targets for regulation by cen-RNAs and confirms the observation that noncoding RNAs play an active role during mitosis (Blower et al, 2005; Du et al, 2010; Ferri et al, 2009; Ideue et al, 2014; Jambhekar et al, 2014; Quenet and Dalal, 2014; Rosic et al, 2014). …”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…My results suggest that a high local concentration of centromeric lncRNAs on mitotic centromeres and chromosomes is an additional pathway for CPC localization and activation that acts in parallel to known pathways of CPC recruitment. Additionally, my results suggest that the CPC is one of the major mitotic targets for regulation by cen-RNAs and confirms the observation that noncoding RNAs play an active role during mitosis (Blower et al, 2005; Du et al, 2010; Ferri et al, 2009; Ideue et al, 2014; Jambhekar et al, 2014; Quenet and Dalal, 2014; Rosic et al, 2014). …”
Section: Discussionsupporting
confidence: 83%
“…Recent work in Drosophila demonstrated that the act of transcription, rather than the resulting RNA, is required for normal Cenp-A deposition (Chen et al, 2015). While several other studies have depleted centromeric RNAs and concluded that cen-RNA is required for various mitotic processes (Ideue et al, 2014; Liu et al, 2015; Quenet and Dalal, 2014; Rosic et al, 2014). Taken together, these studies support the hypothesis that transcription of centromeric DNA plays a role in centromere/kinetochore function through both the process of transcription and through the production of a functional cen-RNA.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Centromeric transcription during mitosis is necessary for kinetochore assembly and function36 and centromeric transcripts are essential for maintaining a functional kinetochore263844454647. Here, we have shown that transcriptional activation coupled with histone H4 acetylation is not sufficient to maintain a functional kinetochore in the absence of H3K4me2.…”
Section: Resultsmentioning
confidence: 85%